A new automated smart cart system for modern shopping centres - Habeeb Bello-Salau; Adeiza James Onumanyi; David Michael; Ridwanullahi Isa; Caroline O. Alenoghena; Henry Ohize (Bulletin of Electrical Engineering and Informatics, 2021)
Modern shopping centres are undoubtedly a beehive of intense shopping activities. However, customers are often plagued by salient challenges, which may include fatigue derived from pushing trolleys around the mall and prolonged sorting of bills by the cashier. These shopping challenges could be daunting for the elderly, disabled, pregnant and nursing mothers. In this paper, we addressed these shopping challenges by developing an autonomous shopping cart with the following characteristics; (1) it follows the customer’s movement relieving the need to push a cart, (2) it bills automatically all stock placed in the cart, (3) it prompts the customer to make payment and updates each stock via a local database. Our design adopts a Raspberry Pi, a camera and a few direct current motors programmed to achieve autonomy. We used an open-source cross platform software called XAMPP to create the database and used RFID tags to bill the items placed in the cart automatically. The system updates payments and communicates these transactions to a local database via nRF24 wireless transceivers. The experimental tests conducted demonstrate that our system successfully followed customers accurately within the mall. We consider our design a major contribution to the vision of automated shopping systems for the near future.